Natalizumab Treatment Modulates Peroxisome Proliferator-Activated Receptors Expression in Women with Multiple Sclerosis - Véronique Ferret-Sena; Alexandra Maia e Silva; Armando Sena; Inês Cavaleiro; José Vale; Bruno Derudas; Giulia Chinetti-Gbaguidi; Bart Staels (PPAR Research)
Peroxisome Proliferator-Activated Receptors (PPAR) are transcription factors suggested to be involved in inflammatory lesions of autoimmune encephalomyelitis and multiple sclerosis (MS). Our objective was to assess whether Natalizumab (NTZ) therapy is associated with alterations of PPAR expression in MS patients. We analyzed gene expression of PPAR in peripheral blood mononuclear cells (PBMC) as well as blood inflammatory markers in women with MS previously medicated with first-line immunomodulators (baseline) and after NTZ therapy. No differences in PPARα, PPARβ/δ, PPARγ, and CD36 mRNA expression were found in PBMC between patients under baseline and healthy controls. At three months, NTZ increased PPARβ/δ mRNA (p=0.009) in comparison to baseline, while mRNA expression of PPARγ and CD36 (a well-known PPAR target gene) was lower in comparison to healthy controls (p=0.026 and p=0.028, resp.). Although these trends of alterations remain after six months of therapy, the results were not statistically significant. Osteopontin levels were elevated in patients (p=0.002) and did not change during the follow-up period of NTZ treatment. These results suggest that PPAR-mediated processes may contribute to the mechanisms of action of NTZ therapy.